THE RELATIONSHIP BETWEEN READING ACHIEVEMENT AND METACOGNITIVE READING STRATEGIES OF EFL STUDENTS AT ISLAMIC BOARDING SCHOOL - Susilo, Dinantari; Widiati, Utami; Wulyani, Anik Nunuk (Jurnal Visi Ilmu Pendidikan, 2026)
This study focuses on the immersion foreign language development program at an Islamic boarding school in Pasuruan, examining how EFL students use metacognitive reading strategies and how these relate to their reading achievement. Quantitative data were collected from an adapted Survey of Reading Strategies (SORS) and reading scores of 58 students from two assessments (the language program and an independent observer). The findings indicate that students generally view themselves as frequent users of metacognitive strategies, supported by a mean SORS score of 3.7, with the highest use in Problem-Solving strategies (M = 4.026). However, no significant correlation was found between Problem-Solving strategies and reading achievement. In contrast, significant relationships emerged between language program test scores and specific strategies such as Overviewing, Guessing, and Information Dealing. The study emphasizes the need to integrate metacognitive strategy training into reading instruction to support comprehension and learner autonomy among EFL students in boarding school environments.